Coenzyme Q-pool function in glycerol-3-phosphate oxidation in hamster brown adipose tissue mitochondria - Rauchová, H; Battino, M; Fato, R; Lenaz, G; Drahota, Z (Journal of bioenergetics and biomembranes, 1992)
We have investigated the role of the Coenzyme Q pool in glycerol-3-phosphate oxidation in hamster brown adipose tissue mitochondria. Antimycin A and myxothiazol inhibit glycerol-3-phosphate cytochrome c oxidoreductase in a sigmoidal fashion, indicating that CoQ behaves as a homogeneous pool between glycerol-3-phosphate dehydrogenase and complex III. The inhibition of ubiquinol cytochrome c reductase is linear at low concentrations of both inhibitors, indicating that sigmoidicity of antimycin A and myxothiazol inhibition is not a direct property of antimycin A and myxothiazol binding. Glycerol-3-phosphate cytochrome c oxidoreductase is strongly stimulated by added CoQ3, indicating that endogenous CoQ is not saturating. Application of the pool equation for nonsaturating ubiquinone allows calculation of the Km for endogenous CoQ of glycerol-3-phosphate dehydrogenase of 3.14 mM. The results of this investigations reveal that CoQ behaves as a homogeneous pool between glycerol-3-phosphate dehydrogenase and complex III in brown adipose tissue mitochondria; moreover, its concentration is far below saturation for maximal electron transfer activity in comparison with other branches of the respiratory chain connected with the CoQ pool. HPLC analysis revealed a lower amount of CoQ in brown adipose mitochondria (0.752 nmol/mg protein) in comparison with mitochondria from other tissues and the presence of both CoQ9 and CoQ10.
Keywords: Mitochondria; Glycerolphosphate Dehydrogenase; Glycerophosphates; ubichinon; Mesocricetus; Carbohydrate Dehydrogenases; antimycin A; Antimycin A; křeček rodu Mesocricetus; methakryláty; palmitoylkoenzym A; karbohydrátdehydrogenasy; Electron Transport Complex III; Thiazoles; oxidace-redukce; hnědá tuková tkáň; Cricetinae; thiazoly; Animals; křečci praví; glycerolfosfátdehydrogenasa; respirační komplex III; zvířata; Ubiquinone; Oxidation-Reduction; Methacrylates; Adipose Tissue, Brown; Palmitoyl Coenzyme A; mitochondrie; glycerolfosfáty